Genetic Parameter Estimates of Body Weights of Naked Neck Broiler Chickens - Adeyinka, I.A.; Oni, O.O.; Nwagu, B.I.; Adeyinka, F.D. (International Journal of Poultry Science, 2006)
The chicks used in this experiment were obtained from a population of naked neck broiler chickens that has been kept in NAPRI since 1998. Six Hundred chicks were obtained from four hatches, one week apart. At hatch, pedigreed chicks were wing-banded and housed on deep litter in an open house. Body weights were measured biweekly up to 8 weeks of age. Other measurements taken include Neck length, Back length, keel length and breast angle. The general least square means were 37.22 ± 0.32, 210.46 ± 1.97, 744.33 ± 4.31, 1351.3 ± 7.91 and 2428.1 ± 14.61g for wt at day old (WT0D), weight at 2 weeks (WT14D), weight at 4 weeks (WT28D), weight at 6 weeks (WT42D) and weight at 8 weeks (WT56D), respectively. While measurements taken included Neck length, Back length, keel length and breast which were 7.31 ± 0.06, 15.99 ± 0.05, 5.63 ± 0.04, 10.44 ± 0.04cm respectively. The heritability estimates ranged from low value of 3.013 ± 0.08 for keel length to 0.315 ± 0.22 for WT0D. There were negative genetic correlations between WT0D and other traits. This study showed that additive heritabilities are low for linear body measurement and moderate for body weight for naked neck chickens during rearing.